2003
DOI: 10.1242/dev.00706
|View full text |Cite
|
Sign up to set email alerts
|

Glypican 4 modulates FGF signalling and regulates dorsoventral forebrain patterning inXenopusembryos

Abstract: Heparan sulphate proteoglycans such as glypicans are essential modulators of intercellular communication during embryogenesis. In Xenopus laevis embryos, the temporal and spatial distribution of Glypican 4 (Gpc4) transcripts during gastrulation and neurulation suggests functions in early development of the central nervous system. We have functionally analysed the role of Xenopus Gpc4 by using antisense morpholino oligonucleotides and show that Gpc4 is part of the signalling network that patterns the forebrain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 49 publications
(86 reference statements)
3
69
1
Order By: Relevance
“…We have also shown that loss-of Gpc4 function in Xenopus embryos impairs forebrain patterning and cell survival from early neural plate stages onwards, and that these early developmental defects result in brains affected by microcephaly at later stages ( Fig. 2; Galli et al, 2003). Xgly4 physically interacts with Wnt11, and might enhance function in the Wnt/PCP pathway during gastrulation (Ohkawara et al, 2003).…”
Section: Glypicans As Modulator Of Regulatory Extra-cellular Signalsmentioning
confidence: 77%
See 2 more Smart Citations
“…We have also shown that loss-of Gpc4 function in Xenopus embryos impairs forebrain patterning and cell survival from early neural plate stages onwards, and that these early developmental defects result in brains affected by microcephaly at later stages ( Fig. 2; Galli et al, 2003). Xgly4 physically interacts with Wnt11, and might enhance function in the Wnt/PCP pathway during gastrulation (Ohkawara et al, 2003).…”
Section: Glypicans As Modulator Of Regulatory Extra-cellular Signalsmentioning
confidence: 77%
“…In addition to Wnt11, we have demonstrated that Xgly4 also binds Fgf2. Inhibition of Fgf signalling results in dorsal forebrain phenotypes similar to those of Xgly4 depleted embryos, indicating that establishment and patterning of the dorsal forebrain territory may require modulation of Fgf signalling by Xgly4 (Galli et al, 2003). Fig.…”
Section: Glypicans As Modulator Of Regulatory Extra-cellular Signalsmentioning
confidence: 82%
See 1 more Smart Citation
“…We also identified Xenopus Glypican-4 (Xgly-4), which belongs to the family of heparan sulphate proteoglycans linked to the cell surface via a glycosylphosphatidylinositol (GPI) anchor; Xgly-4 acts as a co-receptor for Wnt and FGF signals and in this way affects convergence-extension movements during gastrulation and dorsoventral patterning of the forebrain, respectively (Ohkawara et al, 2003;Galli et al, 2003). Lunatic Fringe (lFng) was isolated twice.…”
Section: Previously Characterized Xenopus Proteinsmentioning
confidence: 99%
“…Furthermore, they bind to and control the biological function of signaling molecules, such as growth factors and morphogens (Allen and Rapraeger, 2003;Johnson et al, 2004;Kreuger et al, 2006). These interactions with signaling molecules underlie in part the importance of HSPGs in development (Lin et al, 1999;Galli et al, 2003;Bornemann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%